Evasion from many pursuers in simple motion differential game with integral constraints. - Ibragimov, Gafurjan I.; Salimi, Mehdi; Massoud, Amini (Elsevier, 2012)
We study a two dimensional evasion differential game with several pursuers and one evader with integral constraints on control functions of players. Assuming that the total resource of the pursuers does not exceed that of the evader, we solve the game by presenting explicit strategy for the evader which guarantees evasion.